Determination of Heat Transfer Coefficient and Quality Characteristics of Pasteurised Pink Guava (Psidium Guajava L., Variety Beaumont-30) Juice Drink with Different Brix - Samicho, Zainal (2001)
Heat transfer plays a key role in the production of good quality pasteurised fruit juice drink. Knowledge of heat transfer during the pasteurisation process and the necessity of analysing the data quantitatively have become increasingly important in modern pasteurisation technology. The importance of heat transfer in the production of comfort heating was readily apparent. Heat transfer was not only important in designing the pasteurisation equipment but it was also important in the optimisation of the pasteurisation process for the production of high quality fruit juice drink. Several properties of fruit juice drink such as the microbial, enzyme and sucrose contents, cloud stability and ascorbic acid are greatly affected by heat transfer during pasteurisation. The effect of various operating conditions of pasteurisation on the thennophysical properties (density, thermal conductivity, specific heat capacity,consistency coefficient and flow behaviour index) of pink guava juice drink was investigated. Pink guava juice drink with different total soluble solids (9⁰Brix and 11⁰Brix) at pH 3.7 with an average particle size of 0.355 mm was used in this study. The pink guava (Psidium guajava L.) variety Beaumont: B-30 was supplied by the Golden Hope Plantation, Kulai, lohore, Malaysia. All pasteurisation experiments were performed by using a pilot plant heat exchanger (APV tubular pasteuriser), which was operated at different temperatures and mass flow rates or holding times. During storage at 5⁰C and at room temperature, the quality of the juice drink pasteurised at different conditions, measured as pectinesterase activity, cloud stability, microbial population, sugar and ascorbic acid contents, was analysed. The data gathered from this study were used to develop models which could be employed to describe the variation in the physical properties of pink guava juice drink with different total soluble solids as a function of the pasteurisation operating temperature. The heat transfer coefficient models which related to mass flow rate for laminar flow were also developed. Such models are useful for the simulation process, so that the rate of heat transfer to the juice drink and the quality of the pasteurised juice drink at different pasteurisation operating conditions could be predicted. The models could also be used in designing the pasteurisation set up and the optimisation of the pasteurisation process with a great reduction in the number of experimental runs to be carried out.